Selected poems, 1923-1975 - Warren, Robert Penn 1905-1989 (New York, United States Random House, Inc., 1976)
A collection of Robert Penn Warren's poetry, including ten new poems that have never appeared in book form and the works in previous volumes: "Selected Poems: 1923-1966," "Or else," "Incarnations," and "Audubon."
Keywords: Poetry